SIKAP DAN PERSEPSI PETANI TEMBAKAU DI KABUPATEN TEMANGGUNG TERHADAP BUDIDAYA TANAMAN STEVIA DAN JABON SEBAGAI KOMODITAS ALTERNATIF SELAIN TEMBAKAU - Kanthi Pamungkas Sari; Retno Rusdjijati; Nugroho Agung Prabowo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
ABSTRACT The objective of the study is to determine the attitudes and perceptions of tabacco farmers in Temanggung regency towards stevia and jabon cultivation as an alternative plants beside tobacco, and find out whether the social and economic factors influence the attitudes and perceptions. As the study sample are tobacco armers in the district of Bulu, Tembarak, and Waterford. It is taken 70 samples in every district consisting of 10 villages, so that it is required 210 samples wholly. As an initial step of this research activity is carrying out the socialization to the samples of both commodities offered. Next, the in-depth interviews and questionnaires filling to and by the samples are carried out. The data obtained is processed by using the method of Spearman rho. The data analysis result shows that the tobacco farmers attitudes and perceptios towards cultivation of stevia as an alternative commodity besides tobacco have a good category, while the attitudes and perceptions of tobacco farmers towards the cultivation of jabon as the alternative commodity to tobacco have and adequate category. Social statsushas a positive correlation at a significance level of 5 percent toward the attitudes and perceptions of farmers that is equal to 0,157, and economic status also has a positive correlation toward the attitudes and perceptions of farmers that is equal to 0,220.